Popularizing the Indigenous or Indigenizing the Popular? Television, Video and Fusion Music in Indonesia - R. Anderson Sutton (Wacana Seni Journal of Arts Discourse, 2002)
Music in Indonesia has undergone numerous innovations and experiments over the last 150 years, including various attempts to combine disparate styles and genres. Only in the last decade, however, has this kind of creative exploration come before the wider public, gaining unprecedented support and interest. This paper is an inquiry into what I call "ethno-pop fusion"-music that combines elements of one or more indigenous "traditional" music with elements of Western-style "pop" music. I am particularly concerned with the broad exposure provided for this music by television and, now, video compact discs (VCDs). Beyond the sonic dimension, I believe the visual appeal or the juxtaposition or indigenous "traditional" instruments and players with those of the Western-influenced pop sphere makes these genres especially attractive to television and VCD producers.